Arcangelisia flava LEAVES ETHANOLIC EXTRACT SUPPRESSES CANCER CELL LINES VIA NON APOPTOTIC PATHWAY - Endah Puspitasari; Dian Agung Pangaribowo; Yora Utami; Ika Yanuar Isparnaning (UNEJ e-Proceeding)
Arcangelisia flava is a potential candidate to bedeveloped as cancer chemoprevention agent. A.flava was proven to exhibit antioxidant and cytotoxicactivity against MCF-7 breast cancer cell line. Theseability were suggested to be related to its alkaloidcontent: berberine, palmatine, and jatrorrhizine(Keawpradub et al., 2005). Although this plant isstated as a rarely found species (Koran Jakarta,2012), we could find it abudantly in Meru BetiriNational Park, Jember.Our previous studies showed that A. flava leavesincrease the immune system in doxorubicin-treatedrats (Puspitasari et al., 2014b) with no signs oftoxicity based on sub chronic toxicity assay(Puspitasari et al., 2014a). The A. flava leavesethanolic extract (EEAfL) had been proven to havecytotoxic activity on HeLa, MCF-7, and WiDr cancercell lines with the IC50 value of 467 + 70; 136 + 17;and 213 + 79 μg/ml, respectively. The activity wasselective on MCF-7 and WiDr, but not likely on HeLacell line (Puspitasari et al., 2015).OBJECTIVESThis study was conducted to determine whether thecytotoxic activity of EEAfL was occur via apoptotic ornecrotic pathway using flowcytometry annexin VFITCmethod. The concentration used for the assaywere concentration approx. the IC50 and the IC75based on previous study (Puspitasari et al., 2015).